2008
DOI: 10.1136/thx.2007.078857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of a rapid lung-orientated immunoassay in individuals with possible tuberculosis

Abstract: Background: Immunological ex vivo assays to diagnose tuberculosis (TB) have great potential but have largely been blood-based and poorly evaluated in active TB. Lung sampling enables combined microbiological and immunological testing and uses higher frequency antigenspecific responses than in blood. Methods: A prospective evaluation was undertaken of a flow cytometric assay measuring the percentage of interferon-c synthetic CD4+ lymphocytes following stimulation with purified protein derivative of Mycobacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
8
32
1
Order By: Relevance
“…Although the results of this study are not as clear cut as in the pilot trial, the sensitivity and specificity of the BAL ELISpot for the detection of sputum AFB smear-negative pulmonary TB were 91 and 80%, respectively. The diagnostic accuracy of this BAL ELISpot assay for the diagnosis of sputum AFB smear-negative pulmonary TB is comparable with results from a recent trial using a technically more demanding flow cytometry assay (30).…”
Section: Discussionsupporting
confidence: 63%
“…Although the results of this study are not as clear cut as in the pilot trial, the sensitivity and specificity of the BAL ELISpot for the detection of sputum AFB smear-negative pulmonary TB were 91 and 80%, respectively. The diagnostic accuracy of this BAL ELISpot assay for the diagnosis of sputum AFB smear-negative pulmonary TB is comparable with results from a recent trial using a technically more demanding flow cytometry assay (30).…”
Section: Discussionsupporting
confidence: 63%
“…This procedure has the advantage of being able to sample specific sites (and hence in theory improve the recovery from, e.g., localized disease or a cavity) (Schoch et al 2007). A good-quality sample, which is promptly set up for mycobacterial culture, has a high diagnostic yield (Breen et al 2008b). This is important because the procedure is associated with significant up-front capital cost, and potential risk to both patients and health-care workers.…”
Section: Postprimary Pulmonary Tbmentioning
confidence: 99%
“…Recently, it has been shown that mononuclear cells (MCs) compartmentalized in infected sites such as pleural fluid (8,14) or bronchoalveolar lavage fluid (3,5) have higher gamma interferon responses than peripheral blood mononuclear cells (PBMCs). We aimed to demonstrate the proof of concept for the ability of the enzyme-linked immunospot (ELISPOT) assay to differentiate active TB from latent TB using compartmentalized lymphocytes.…”
mentioning
confidence: 99%